2019
DOI: 10.3892/ol.2019.10726
|View full text |Cite
|
Sign up to set email alerts
|

Non‑invasive detection of EGFR and TP53�mutations through the combination of plasma, urine and sputum in advanced non‑small cell lung cancer

Abstract: The sensitivity and utility of liquid biopsy in clinical practice requires some improvement. The aim of the present study was to improve the detection of epidermal growth factor (EGFR) and cellular tumor antigen p53 (TP53) mutations in liquid biopsies from patients with advanced non-small cell lung cancer (NSCLC) by combining plasma, sputum and urine samples under the same sequencing platform. Plasma, sputum and urine samples, and tumor tissues were obtained from 50 patients with NSCLC and were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Fei et al collected spontaneous sputum in a 1.5 mL container [28]. Wu et al collected approximately 5 mL of spontaneous sputum in a mixed solution with an equal volume of Saccomanno's xative and 0.005% dithiothreitol solution at a 1:1 ratio [29,37]. We collected spontaneous sputum using the YM…”
Section: Discussionmentioning
confidence: 99%
“…Fei et al collected spontaneous sputum in a 1.5 mL container [28]. Wu et al collected approximately 5 mL of spontaneous sputum in a mixed solution with an equal volume of Saccomanno's xative and 0.005% dithiothreitol solution at a 1:1 ratio [29,37]. We collected spontaneous sputum using the YM…”
Section: Discussionmentioning
confidence: 99%
“…Fei et al collected spontaneous sputum in a 1.5 mL container [28]. Wu et al collected approximately 5 mL of spontaneous sputum in a mixed solution with an equal volume of Saccomanno's xative and 0.005% dithiothreitol solution at a 1:1 ratio [29,37]. We collected spontaneous sputum using the YM…”
Section: Discussionmentioning
confidence: 99%
“…Su, et al performed ampli cation refractory mutation system (ARMS)-PCR for 35 sputum samples containing tumor cells collected from stage III-IV lung cancer patients and reported a 90.9% sensitivity [28]. Wu et al reported a 63% sensitivity when an EGFR sensitizing mutation was analyzed in 50 sputum samples using next-generation sequencing [29]. Presently, ddPCR analysis of 80 sputum samples revealed an 80.0% detection sensitivity for EGFR mutations if the sputum cytology was positive.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both plasma and urine ctDNA could be utilized as markers of colorectal cancer progression [ 160 ]. Similarly, the detection of EGFR and TP53 mutations through the combination of plasma, urine, and sputum could improve the predictive value of personalized treatment of advanced NSCLC [ 161 ]. However, sensitive and accurate methods allowing high depth of sequencing and minimization of artifacts are required for the molecular detection of mutations in urinary DNA.…”
Section: Other Liquid Biopsy Typesmentioning
confidence: 99%